KEBIJAKAN TERHADAP PELAKU ANAK TINDAK PIDANA PEMBUNUHAN BERENCANA - Juwita, Indah; Nurunnisa (The Juris, 2024)
Technological advances have had a changing impact on social life, especially the use of the internet which makes everything limitless so that anyone can access things easily, including children. Several things that are on the internet are then accessed by children without parental supervision, which is one of the factors that makes a child a perpetrator of a crime. Various criminal acts are committed by children, including children as perpetrators of premeditated murder. In cases of premeditated murder committed by children, there are several provisions that differentiate those committed by adults, all of this is related to the judge's decision in the end. Law Number 23 of 2002 concerning Children becomes the legal basis in addition to the Criminal Code and Criminal Procedure Code when a child is the perpetrator of a criminal act of premeditated murder. This research focuses on discussing policies regarding the crime of children as perpetrators of premeditated murder. The research method used is normative legal research and uses a statutory approach (statue approach) and conceptual approach (conceptual approach).